Kontribusi Pendidikan Islam Dalam Pembentukan Dai Muda Yang Berkualitas Dalam Menyebarkan Dakwah Islami - Nurjamilah; Nazwa, Rinni; Abdillah, Raka (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2024)
Islamic education plays a crucial role in shaping the character and quality of an effective young preacher (dai) in disseminating Islamic preaching. This article examines the contribution of Islamic education in forming quality young preachers, focusing on key aspects that build the foundation of knowledge, ethics, and preaching skills. The research aims to analyze the contribution of Islamic education in shaping the quality of young preachers in spreading Islamic preaching. The research methodology involves literature review, interviews, and content analysis. The findings indicate that Islamic education provides a solid knowledge base, fosters good moral character, and enhances the preaching skills of young preachers. Well-educated young preachers can act as positive agents of change in society, effectively disseminating the message of Islam and responding to contemporary challenges in line with Islamic values. This research provides a profound understanding of the role of Islamic education in shaping a generation of quality preachers.